Improving Science Learning Activities and Outcomes by Using Problem Based Learning Model at Elementary School - Saleh, Ahmad; Ahda, Yuni; Fitria, Yanti (Jurnal Basicedu, 2020)
Science learning requires direct experience in order to develop the ability to explore and understand the natural surroundings scientifically. So far in elementary school at Bukittinggi, the process of learning science only memorizes facts, principles or theories. In science learning, students are not involved in finding or applying their own ideas and they do not instill the values contained in the learning. The science learning process in classroom is not yet fully in accordance with the demands of the curriculum. The teacher provides more material in the textbook without relating it to students' daily problems that are in accordance with the material, thus causing less interesting in learning. The teacher also has not actively involved all students in learning and emphasizes learning only on students who are smarter. The purpose of this study was to increase the activity and learning outcomes of science learning by using a problem-based learning model in SDN 11 Aur Kuning Bukittinggi, West Sumatra. This classroom action research was conducted in 2 cycles with the research subjects of grade IV students with totalling 25 people. The research data were collected through observation and tests. The effectiveness of actions in each cycle from the results of observations and tests is described and then reflected to take corrective action in the next cycle. In science learning, students' learning activities were observed, namely: visual activities, oral activities, writing activities, motoric activities and emotional activities. The research findings show that the problem-based learning model can increase student activity and learning outcomes.